Impact Of Positive News On Stock Prices Of Pharmaceutical Sector In Nse During Covid-19 - Sharma, Navneet; Sharma, Dr. Trishu (The journal of contemporary issues in business and government, 2021)
COVID-19 has hit the global economy and the emotions of the world stock market tremendously. Indian Financial market faced a deep steep based on global cues and just before the lockdown in India. Sharp volatility was observed on daily basis but since long an underperforming pharmaceutical sector substantially increased globally based on news. The research tries analysing how positive news has helped pharmaceutical sector stocks to become multibaggers during pandemic. The sample period taken for the study is 6 months from (January, 2020- June, 2020) three months before lockdown and three months after lockdown in India. The index was 41, 306 on January 1, 2020 and on the day of lockdown March 25, 2020 index has fallen to 28, 535 but still it helped pharmaceutical sector to grow substantially.